Optimisation of PC12 Cell-based In Vitro Stroke Model for Screening of Potential Neuroprotective Agents - Chua, Pin Fen (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Stroke is one of the commonest causes of death and disability worldwide. To date, no neuroprotective agent is approved clinically for treatment of acute ischaemic stroke. PC12 cell-based in vitro stroke model has been used widely to screen for neuroprotective agents. The most common approach is to differentiate PC12 cells into a neuronal phenotype and subject the differentiated cells to oxygen glucose deprivation (OGD) to simulate an ischaemic stroke. However, there are increasing reports showing certain PC12 cell variants either poorly or cannot differentiate into neuron-like cells. Additionally, optimisation studies for cell culture media and adhesive substrate for commonly-used PC12 variants are limited. This study aimed to optimise cell culture conditions of three commonly-used PC12 cell variants and test their response to nerve growth factor (NGF)-induced differentiation. PC12 cells (Riken cell bank), PC12 Adh cells and PC12 Neuroscreen-1 (NS-1) cells were studied. Optimisation of cell culture media and adhesive substrates were done by comparing cell morphology in different media and substrates. Adaptation of the three PC12 cell variants to a serum-free supplemented media was necessary because drug intervention studies need to be done in the absence of serum to avoid confounding effects. Comparison of the NGF-induced differentiation for the three PC12 cell variants was done by counting the percentage of neurite-bearing cells. The PC12 variant with the highest response to NGF underwent studies to optimise its duration of OGD. Differentiated-cells were subjected to different durations of OGD followed by measurement of cell viability and enzyme activity in the execution phase of apoptosis (caspase 3 and 7) to determine the optimal duration of OGD for in vitro stroke model. The in vitro model was validated by treating the OGD-treated cells with a known neuroprotectant, 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) for 24 hours. The optimal culture media for PC12 cells (Riken) and NS-1 cells was found to be DMEM high glucose. Collagen IV was the best substrate for PC12 cells (Riken) and NS-1 cells. PC12 Adh cells showed no preference for media or substrates. Both NS-1 cells and PC12 cells (Riken) were successfully adapted to serum-free supplemented media. However, PC12 Adh cells failed to grow in a serum-free supplemented media. NS-1 cells gave the highest NGF-induced differentiation (72.7 ± 9.1%) followed by PC12 cells (Riken, 36.0 ± 5.6%) and PC12 Adh cells (6.9 ± 0.8%). NS-1 cells achieved optimal differentiation after three days of 150 ng/mL NGF treatment. The optimal duration of OGD to induce cell injury was three hours. Treatment with 8-OH-DPAT on NGF-differentiated NS-1 cells after three hours of OGD showed a significant reduction in apoptosis (p < 0.01, One-way ANOVA followed by post hoc Tukey's test). In conclusion, we have shown that each PC12 variant has differing requirements for media and adhesive substrates. NS-1 cells were the optimal PC12 cell variant for an in vitro stroke model due to its high level of NGF-induced differentiation. DMEM high glucose was the optimal media and collagen IV was the best substrate for NS-1 cells. We also provide the first report that 8-OH-DPAT is neuroprotective in NS-1 cells. We conclude that we have optimised and set up an in vitro stroke model to screen for potential neuroprotective agents.